2006
DOI: 10.1080/01913120600854269
|View full text |Cite
|
Sign up to set email alerts
|

Value of the Innovated Technique Agarose Cell Block in Improving the Sensitivity of Urine Cytology in Cases of Bladder Carcinoma

Abstract: Proper handling and processing of urine sample can greatly improve diagnostic sensitivity. This work investigates the value of agarose cell block technique in processing urine samples simultaneously for light and electron microscopic examination, with the prospect to enhance the quality of diagnosis. The material of this study consisted of 45 voided urine samples, processed for the performance of Papanicolaou-stained urine smears, agarose cell blocks paraffin sections stained with hematoxylin & eosin, and elec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 16 publications
1
9
0
1
Order By: Relevance
“…The cooled, solidified agar lump is easily falling out of the tube when turned upside down, if not formalin or saline can be injected under it with a small needle. The lump then floats to the top of the tube [22, 23]. Heat artifacts from molten agarose heating processing affect morphology [24].…”
Section: The Agarose Methodsmentioning
confidence: 99%
“…The cooled, solidified agar lump is easily falling out of the tube when turned upside down, if not formalin or saline can be injected under it with a small needle. The lump then floats to the top of the tube [22, 23]. Heat artifacts from molten agarose heating processing affect morphology [24].…”
Section: The Agarose Methodsmentioning
confidence: 99%
“…CB provides more pathological information, when combined with histological examination such as hematoxylin and eosin (H&E) staining and immunostaining of serial sections compared with each method alone. Several studies have reported that CB improves diagnostic efficacy, and the implementation of immunocytochemistry is remarkably useful for the discovery of non-morphological markers [6], [7]. However, very few studies have evaluated and summarized the performance of these 3 methods in the examination of EUS-FNA samples.…”
Section: Introductionmentioning
confidence: 99%
“…Our criteria for calling cell lines as SCLC were as follows: (I) pathological diagnosis of SCLC of the original diagnostic material; (II) cell culture with the growth properties characteristic of SCLC; (III) morphological features of classic or variant SCLC by examination of formalin fixed, paraffin embedded agarose cell blocks (20) or cell line derived xenografts (CCXs); and (IV) loss of Rb protein expression by Western blotting (21), or inactivating mutations of the RB1 gene by sequencing. As rare SCLC tumors lack inactivation of RB1 (17), in one case we identified a cell line with intact Rb protein expression as SCLC.…”
Section: Identification Of Sclc Cell Linesmentioning
confidence: 99%